2014
DOI: 10.1148/radiol.14140806
|View full text |Cite|
|
Sign up to set email alerts
|

Myocardial CT Perfusion Imaging and SPECT for the Diagnosis of Coronary Artery Disease: A Head-to-Head Comparison from the CORE320 Multicenter Diagnostic Performance Study

Abstract: Purpose:To compare the diagnostic performance of myocardial computed tomographic (CT) perfusion imaging and single photon emission computed tomography (SPECT) perfusion imaging in the diagnosis of anatomically significant coronary artery disease (CAD) as depicted at invasive coronary angiography. Materials and Methods:This study was approved by the institutional review board. Written informed consent was obtained from all patients. Sixteen centers enrolled 381 patients from November 2009 to July 2011. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 32 publications
(23 reference statements)
0
41
0
3
Order By: Relevance
“…The combination of CCTA and CTP has increased diagnostic accuracy of CCTA for the diagnosis of hemodynamically significant coronary stenosis [6365]. CT myocardial stress perfusion imaging has recently been shown to be more accurate than SPECT for the diagnosis of CAD [66]. Combining CTA and CTP yielded and AUC of 0.87 for predicting CAD by conventional angiography which was associated with a corresponding myocardial perfusion defect by SPECT [67].…”
Section: New Technologic Developmentsmentioning
confidence: 99%
“…The combination of CCTA and CTP has increased diagnostic accuracy of CCTA for the diagnosis of hemodynamically significant coronary stenosis [6365]. CT myocardial stress perfusion imaging has recently been shown to be more accurate than SPECT for the diagnosis of CAD [66]. Combining CTA and CTP yielded and AUC of 0.87 for predicting CAD by conventional angiography which was associated with a corresponding myocardial perfusion defect by SPECT [67].…”
Section: New Technologic Developmentsmentioning
confidence: 99%
“…54 There are extensive CTP data favorably comparing its accuracy to ICA, MPI, and stress MRI for the detection of >50% stenosis by ICA. [55][56][57][58] The ability to reduce false-positive findings by discounting perfusion abnormalities in the distribution of normal vessels offers an advantage over the other functional tests, all of which lack an anatomic component. There are several studies comparing CTP with invasive FFR (Table 4).…”
Section: Ct Myocardial Perfusion Imagingmentioning
confidence: 99%
“…In the CORE320 study, George et al showed that the diagnostic performance of single-phase stress perfusion CT imaging is higher than that of SPECT for the identification of patients with a stenosis of more than 50% on ICA, an improvement mostly driven by a higher sensitivity of CT [25]. Interestingly, the combination of single-phase stress CT with CTA provided even better diagnostic accuracy in several studies, which makes combination of these techniques into one scan examination promising for future patient workup [22,[36][37][38].…”
Section: Stress Vs Restmentioning
confidence: 99%